ON THE BASIS OF INNOVATIVE DEVELOPMENT OF INTELLECTUAL POTENTIAL OF CHILDREN WITH A QUALITY EDUCATION ORGANIZATION (Academia Science Repository, 2023)
In the article of preschool age children increasing the mental capacity of about innovative approaches that can be used the word will go. Potential caregivers need to be taken into account in the preparation of the quality of education the word about the aspects that I mentioned. Also, young children approach them on the basis of specific features in small individual issues, problematic circumstances, and given thoughts about methods to eliminate them. From this article the potential of pre-school education and improving the capacity of caregivers can use their professional organizations.